MENINGKATKAN KEMAMPUAN PENALARAN SISWA SMP NEGERI 11 PEMATANGSIANTAR MELALUI MODEL PEMBELAJARAN MATEMATIKA REALISTIK - Rianita Simamora; Yanty Maria Rosmauli Marbun (MES: Journal of Mathematics Education and Science, 2023)
Learning mathematics is intended so that students are able to use reasoning in identifying, analyzing and concluding a pattern and character of a mathematical object. In addition, by manipulating mathematics students will be able to generalize a concept, compile evidence or explain mathematical ideas and statements. The purpose of this study is to determine the increase in reasoning ability that occurs after implementing a realistic mathematics learning model. This study refers to a quasi-experimental research procedure with a pretest-posttest approach. The population used in this study were all students of class VIII SMP Negeri 11 Pematangsiantar with the sample being all students of class VIIIB, totaling 21 people. The instrument used in this study was a learning achievement test in the form of multiple choice objective tests with four options totaling 24 questions. The results showed that during the pre-test the average score of students was at 64.45 with a standard deviation of 4.575 and experienced an increase during the post-test with an average of 80.25 and a standard deviation of 6.25. In addition, when viewed from the completeness of learning there is also an increase, namely from 57.14 to 80.95.